Efficacy of next treatment received after nivolumab progression in patients with advanced nonsmall cell lung cancer. Issue 2 (20th April 2018) - Costantini, Adrien; Corny, Jennifer; Fallet, Vincent; Renet, Sophie; Friard, Sylvie; Chouaid, Christos; Duchemann, Boris; Giroux-Leprieur, Etienne; Taillade, Laurent; Doucet, Ludovic; Nguenang, Marina; Jouveshomme, Stéphane; et al.
Nivolumab for the treatment of advanced nonsmall cell lung cancer (NSCLC) evaluated in phase III trials showed 50% progression at first evaluation, but better overall survival (OS), suggesting regained efficacy of treatments given thereafter. We aimed to evaluate the efficacy of nivolumab and of next treatment received after nivolumab progression in patients with advanced NSCLC. Our multicentre retrospective study included all patients receiving nivolumab between January and December 2015. The primary end-point was progression-free survival (PFS) of treatment given after nivolumab. The 303 patients had the following characteristics: median age 63 years, 69% males, 92% smokers, 67% performance status 0–1 and 61% adenocarcinoma. Nivolumab was given as second-line treatment in 40% of patients. With 13.7 months of median follow-up, nivolumab PFS and OS were 2.6 and 11.3 months, respectively. At the cut-off analysis 18% were controlled under nivolumab, 14% were deceased and 5% were lost to follow-up under nivolumab. Among the 191 (63%) patients eligible for post-nivolumab (PN) treatment, 115 (38%) received further treatment and were characterised by better performance status (p=0.028) and by receiving more injections of nivolumab (p=0.001). Global PN-OS and PN-PFS were 5.2 and 2.8 months, respectively. Drugs most frequently used after nivolumab were gemcitabine (23%), docetaxel (22%) and erlotinib (16%), with median PFS of 2.8, 2.7 and 2.0 months, respectively. Nivolumab produced similar efficacy as in phase III trials, although patients received nivolumab later and had worse performance status. 38% received treatment after nivolumab progression with efficacy comparable to historical second-line trials. Efficacy of nivolumab in nonsmall cell lung cancer http://ow.ly/k2uX30iGZbY